Impaired short-term visual paired associative plasticity in patients with migraine between attacks. Issue 3 (March 2021) - Abagnale, Chiara; Ranieri, Federico; Di Renzo, Antonio; Parisi, Vincenzo; Serrao, Mariano; Di Lazzaro, Vincenzo; Lisicki, Marco; Coppola, Gianluca; Pierelli, Francesco
Abstract : Abstract: A common experimental neurophysiological method to study synaptic plasticity is pairing activity of somatosensory afferents and motor cortical circuits, so-called paired associative stimulation (PAS). Dysfunctional inhibitory and excitatory PAS mechanisms within the sensorimotor system were described in patients with migraine without aura (MO) between attacks. We have recently observed that the same bidirectional PAS rules also apply to the visual system. Here, we have tested whether dysfunctioning associative plasticity might characterize the visual system of patients with MO. In 14 patients with MO between attacks and in 15 healthy volunteers, we performed a previously validated visual PAS (vPAS) protocol by coupling 90 black-and-white checkerboard reversals with low-frequency transcranial magnetic stimulation pulses over the occipital cortex at 2 interstimulus intervals of −25/+25 ms around the visual-evoked potential (VEP) P1 latency. We recorded VEPs (600 sweeps) before, immediately after, and 10 min after each vPAS session. We analysed VEP N1-P1 amplitude and delayed habituation. Although vPAS-25 significantly enhanced and vPAS + 25 reduced VEP amplitude habituation in healthy volunteers, the same protocols did not significantly change VEP amplitude habituation in MO between attacks. We provide evidence for lack of habituation enhancing and habituation suppressing visual PAS mechanisms within the visual system in interictal migraine. This finding, in combination with those previously obtained studying the sensorimotor system, leads us to argue that migraine disease-related dysrhythmic thalamocortical activity prevents the occurrence of physiological bidirectional synaptic plasticity induced by vPAS. Abstract : In contrast to controls, in migraineurs, visual paired associative stimulation was ineffective in inducing bidirectional synaptic plasticity on visual-evoked potential habituation.